Preserved landscapes underneath the Antarctic Ice Sheet reveal the geomorphological history of Jutulstraumen Basin. Issue 13 (28th August 2021) - Franke, Steven; Eisermann, Hannes; Jokat, Wilfried; Eagles, Graeme; Asseng, Jölund; Miller, Heinrich; Steinhage, Daniel; Helm, Veit; Eisen, Olaf; Jansen, Daniela
Abstract: The landscape of Antarctica, hidden beneath kilometre‐thick ice in most places, has been shaped by the interactions between tectonic and erosional processes. The flow dynamics of the thick ice cover deepened pre‐formed topographic depressions by glacial erosion, but also preserved the subglacial landscapes in regions with moderate to slow ice flow. Mapping the spatial variability of these structures provides the basis for reconstruction of the evolution of subglacial morphology. This study focuses on the Jutulstraumen Glacier drainage system in Dronning Maud Land, East Antarctica. The Jutulstraumen Glacier reaches the ocean via the Jutulstraumen Graben, which is the only significant passage for draining the East Antarctic Ice Sheet through the western part of the Dronning Maud Land mountain chain. We acquired new bed topography data during an airborne radar campaign in the region upstream of the Jutulstraumen Graben to characterise the source area of the glacier. The new data show a deep relief to be generally under‐represented in available bed topography compilations. Our analysis of the bed topography, valley characteristics and bed roughness leads to the conclusion that much more of the alpine landscape that would have formed prior to the Antarctic Ice Sheet is preserved than previously anticipated. We identify an active and deeply eroded U‐shaped valley network next to largely preserved passive fluvial and glacial modified landscapes. Based on the landscape classification, we reconstruct the temporal sequence by which ice flow modified the topography since the beginning of the glaciation of Antarctica. Abstract : Airborne ice‐penetrating radar data reveal the evolution of the subglacial morphology of the Jutulstraumen Glacier drainage system in western Dronning Maud Land. We identify various geomorphological patterns that are related to different stages of subglacial erosion and allow us to reconstruct the temporal sequence by which ice flow modified the topography since the beginning of glaciation of Antarctica.